Service Climate and Display of Employees’ Positive Emotions: The Mediating Role of Burnout and Engagement in Services - Carrasco, Hugo (2011)
This article aims to test a model linking service climate to the frequency of expression of positive emotions by frontline employees. We propose that burnout and engagement at work mediate the relationship between service climate and the expression of positive emotions. Service climate impacts negatively on burnout and positively on engagement; in turn, burnout and engagement are significantly related to the frequency of expression of positive emotions. This model was tested both at the individual and work-unit levels. In addition, it was compared with a direct model that proposes an additional direct link from service climate to frontline employees’ positive emotions. Models were tested through structural equation modeling. The sample consisted of 508 frontline employees working in 151 work-groups. At the individual level, results confirmed the mediating role of engagement in the relationship between service climate and the expression of frontline employees’ positive emotions. At the work-unit level, both burnout and engagement mediated the relationship between service climate and positive emotions. Engagement was the most important direct predictor of the display of positive emotions, both at the individual and work-unit levels.